Professional Teacher Recruitment Strategy in the Perspective of Human Resource Management and the Qur'an in the Era of Globalisation - Hanuji Akbar; Ismi Durrotul Mamlu’ah; Hanif Firdaus; Erik Junaedi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study aims to examine professional teacher recruitment strategies from the perspectives of Human Resource Management (HRM) and the Qur’an at Madrasah Aliyah Pondok Pesantren Sumber Payung, Sumenep. The study addresses the need for a recruitment model that not only emphasizes managerial effectiveness but also reflects Islamic ethical values. Its main argument is that teacher recruitment in Islamic educational institutions should integrate professional competency standards with Qur’anic principles of justice, responsibility, and trustworthiness. This study employed a qualitative case study approach. Data were collected through in-depth interviews with four key informants, namely the principal, head of administration, recruitment committee member, and student representative. Participant observation and document analysis were also used to strengthen the data. The data were analyzed through thematic analysis involving open coding, categorization, and interpretation. The findings reveal three main results. First, teacher recruitment practices integrate HRM principles, including workforce planning, competency-based selection, and performance evaluation, although the process is still conducted through a kinship-based system rather than open digital recruitment. Second, Qur’anic values, particularly justice and responsibility as khalifah, serve as ethical foundations in recruitment decision-making. Third, this hybrid recruitment model contributes to teacher professionalism, institutional trust, and student learning outcomes. This study implies that Islamic educational institutions need to develop recruitment systems that combine HRM professionalism with Qur’anic ethical values. However, as a single case study, the findings are context-specific and require further comparative research in other Islamic educational institutions.